Snubber resistor influence in the thyristor valves failure on the static VAR compensator. (July 2018) - Arias Velásquez, Ricardo Manuel; Mejia Lara, Jennifer Vanessa
Abstract: In this research, a complex engineering failure analysis is done for a static VAR compensator (SVC), it was installed in Perú 220 kV system. The research introduce the selected results of the simulations and field tests completed during the fault, mitigation and corrective activities performed at the thyristor valve, which is installed in the thyristor switched capacitor (TSC) and thyristor controlled reactor (TCR) of the SVC. This paper proposes the most feasible solution to overcome the failure of the TSC based on snubber resistor in the SVC. In order to investigate the causes of this failure, various measurements were carried out on the TSC. It was concluded that a snubber resistor design needs two special test for determinate a problem or abnormal condition; a special test should be done in the factory acceptance test (FAT), site acceptance test (SAT) and to execute a maintenance diagnosis, to prevent a failure in the thyristor valve from TSC. This failure has happened in the standby system, the susceptance reference is forced to follow the susceptance reference received from the active system. There is however, a delay in the transfer of data from the active to the standby system. During transient conditions this may cause a difference in thyristor firing angles between the systems. The simulated current in the standby system does not agree with the measured current, which is controlled by the active system, an advanced diagnosis and design review is developed for to avoid a sudden failure. The feasibility of these solutions was verified through the computer simulation with PSCAD/EMTDC. Highlights: A SVC sudden failure associated a TSC valve defect has been analyzed. A snubber resistor design has been verified and a proposal test has been descripted. Maintenance and design aspects have been developed.